2013
DOI: 10.4314/ajtcam.v10i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Study on<i>in vitro</i> anti-tumor activity of <i>Bidens bipinnata</i> L. extract

Abstract: We studied the in vitro anti-tumor activity of Bidens Bipinnata L. extract. MTT assay was used to investigate the inhibitory effect of different concentrations of the extracts on human hepatocellular carcinoma (HepG2) cell lines and human cervical carcinoma (Hela) cell lines, and the IC 50 values were calculated. The Bidens Bipinnata L. extract had different degrees of inhibitory effects on these two cells, and when exposure time was 48 h, the inhibition rate reached its peak, with IC 50 values of 14.80 μg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Bidens pilosa primarily grows in the warm and moist environment of southern China and has a relatively long history of being used for treating diseases, such as malaria, diarrhoea, dysentery and hepatitis (25)(26)(27)(28). Recently, extensive studies have found that flavonoids from Bidens pilosa have antitumour effects (29)(30)(31)(32). This discovery indicates that in addition to the aforementioned functions, flavonoids from Bidens pilosa also play an important role in antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bidens pilosa primarily grows in the warm and moist environment of southern China and has a relatively long history of being used for treating diseases, such as malaria, diarrhoea, dysentery and hepatitis (25)(26)(27)(28). Recently, extensive studies have found that flavonoids from Bidens pilosa have antitumour effects (29)(30)(31)(32). This discovery indicates that in addition to the aforementioned functions, flavonoids from Bidens pilosa also play an important role in antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Bidens bipinnata L. has often been used by local people to treat hypertension, hyperlipidaemia, diabetes, and anti-hepatic fibrosis and as an antitumour agent with positive effects. Many studies have proven that the flavonoid compounds of Bidens bipinnata L. have antitumour effects (15)(16)(17)(18)(19)(20). Isoquercitrin is a flavonoid compound isolated from Bidens bipinnata L. Ma et al (21) and Zhong et al (22) demonstrated that the main components of the total flavone of Bidens bipinnata L. are isoquercitrin and hyperin via separation using macroporous adsorption resin and high performance liquid chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that isoquercitrin significantly inhibits the progression of bladder cancer in vivo. efficacies (18)(19)(20). Ma et al (21) and Zhong et al (22) utilized macroporous adsorptive resins and high-performance liquid chromatography (HPLC) to separate the main components of total flavones in Bidens and proved that these components mainly consist of isoquercitrin and hyperoside.…”
Section: Isoquercitrin-mediated Cell Cycle Arrest Of Bladder Cancer Cmentioning
confidence: 99%